2014
DOI: 10.1373/clinchem.2013.210658
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mRNA Splicing Assay Protocols across Multiple Laboratories: Recommendations for Best Practice in Standardized Clinical Testing

Abstract: Background Accurate evaluation of unclassified sequence variants in cancer predisposition genes is essential for clinical management and depends on a multifactorial analysis of clinical, genetic, pathologic, and bioinformatic variables and assays of transcript length and abundance. The integrity of assay data in turn relies on appropriate assay design, interpretation, and reporting. Methods We conducted a multicenter investigation to compare mRNA splicing assay protocols used by members of the ENIGMA (Eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(111 citation statements)
references
References 29 publications
1
106
2
2
Order By: Relevance
“…The corresponding isoform, using the same acceptor site in a wild-type allele, would be the ▾5p alternate-splicing event described here. Although the ▾5p splicing event was not observed previously in RNA samples from LCLs of BRCA1/2 pathogenic variant carriers or controls5 or by contributing members for phase Ia of this study, the isoform-specific RT-PCR analysis revealed this splicing event in 5/10 LCLs, BT20, MCF10A and 184A1 (table 2). …”
Section: Resultscontrasting
confidence: 47%
See 4 more Smart Citations
“…The corresponding isoform, using the same acceptor site in a wild-type allele, would be the ▾5p alternate-splicing event described here. Although the ▾5p splicing event was not observed previously in RNA samples from LCLs of BRCA1/2 pathogenic variant carriers or controls5 or by contributing members for phase Ia of this study, the isoform-specific RT-PCR analysis revealed this splicing event in 5/10 LCLs, BT20, MCF10A and 184A1 (table 2). …”
Section: Resultscontrasting
confidence: 47%
“…In an unrelated study,5 an isoform containing 18 intronic nucleotides upstream exon 5 was reported in a subject carrying a c.426–12_c.426-8delGTTTT that results in the use of a cryptic acceptor site. The corresponding isoform, using the same acceptor site in a wild-type allele, would be the ▾5p alternate-splicing event described here.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations